The impact of political uncertainty on institutional ownership - Bill B. Francis; Iftekhar Hasan; Zhu Yun (Bank of Finland, 2013)
This paper provides original evidence from institutional investors that political uncertainty during presidential elections greatly affects investment. Using U.S. institutional ownership data from 1981 to 2010, we find that institutions significantly reduce their holdings of common stock by 0.76 to 2.1 percentage points during election years. More specifically, institutions tend to sell large proportions of their positions when Republicans win presidential elections and then keep their positions at below-average levels through the first year of the new administration. Conversely, when Democrats win presidential elections, institutions tend to keep their positions at above-average levels for the first year of the new administration. The difference in ownership rises to 2.4% by the end of the first year of new administration. Changes in institutional ownership in election years are sensitive to the uncertainty of the outcome. Our results also show that institutions benefit from these holding strategies during the pre-election periods.
URN:NBN:fi:bof-20140807361
Keywords: G23; G28; P16; 330; political uncertainty; presidential election; institutional investor; investment